The burst‐phase folding intermediate of ribonuclease H changes conformation over evolutionary history. Issue 8 (20th November 2017) - Lim, Shion A.; Marqusee, Susan
Abstract: The amino acid sequence encodes the energy landscape of a protein. Therefore, we expect evolutionary mutations to change features of the protein energy landscape, including the conformations adopted by a polypeptide as it folds to its native state. Ribonucleases H (RNase H) from Escherichia coli and Thermus thermophilus both fold via a partially folded intermediate in which the core region of the protein (helices A‐D and strands 4‐5) is structured. Strand 1, however, uniquely contributes to the T. thermophilus RNase H folding intermediate ( I core+1 ), but not the E. coli RNase H intermediate ( I core ) (Rosen & Marqusee, PLoS One 2015). We explore the origin of this difference by characterizing the folding intermediate of seven ancestral RNases H spanning the evolutionary history of these two homologs. Using fragment models with or without strand 1 and FRET probes to characterize the folding intermediate of each ancestor, we find a distinct evolutionary trend across the family—the involvement of strand 1 in the folding intermediate is an ancestral feature that is maintained in the thermophilic lineage and is gradually lost in the mesophilic lineage. Evolutionary sequence changes indeed modulate the conformations present on the folding landscape and altered the folding trajectory of RNase H. Abstract :